Polypropylene clay nanocomposite :a study of mechanical properties - Muhammad Ilham, Miskon (2010)
Polymer nanocomposites(PNs)is a kind of polymer which fill with the composite with nano size and widely used especially in food packaging,labels,coatings and etc.The properties of Polypropylene can be adjusted by two approaches which is to change its molecule structure by modification of its three basic building blocks(polyether or polyester,diisocyanate, and chain extender)and then,to introduce the inorganic fillers into the polyprpylene matrix.In this project, pure PP will reinforced by adding the Cloisite® C20A at 1wt%,3wt% and 5wt% composites inside PP matrix by melt intercalation method using twin screw extruder, then molded using hot press to prepare samples.Attendance of C20A in polypropylene matrix can be detected by using FTIR at the peak 1580 cm-1. Rockwell Brinell Hardness test was used to study the hardness and the result showed that the hardness increased up to 28%.Universal Mechanical test used to study the tensile of the samples and the result indicates that the strength of the PP with C20A had been improved up to 34%. The results show that,PP with additional of C20A was improved in their mechanical properties due to maximum intercalation and exfoliated between PP and C20A.